2008
DOI: 10.1021/jp800525w
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Diffusion in a Water-in-Oil Microemulsion Loaded with Malonic Acid or Ferroin. Taylor Dispersion Method for Four-Component Systems

Abstract: We describe an improved Taylor dispersion method for four-component systems, which we apply to measure the main- and cross-diffusion coefficients in an Aerosol OT water-in-oil microemulsion loaded with one of the reactants of the Belousov-Zhabotinsky (BZ) reaction, water(1)/AOT(2)/R(3)/octane(4) system, where R is malonic acid or ferroin. With [H(2)O]/[AOT] = 11.8 and volume droplet fraction phi d = 0.18, when the microemulsion is below the percolation transition, the cross-diffusion coefficients D(13) and D(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 55 publications
3
54
0
Order By: Relevance
“…The eluted peak, sometimes called the Taylor peak, is monitored by a suitable detector such as a flow-through spectrophotometer, refractive index detector (RID) or Raman spectrometer. 93,94 The diffusion coefficients are calculated from the parameters of the Gaussian functions that fit the eluted peak. A typical peak is shown in Fig.…”
Section: Cross-diffusion Without Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…The eluted peak, sometimes called the Taylor peak, is monitored by a suitable detector such as a flow-through spectrophotometer, refractive index detector (RID) or Raman spectrometer. 93,94 The diffusion coefficients are calculated from the parameters of the Gaussian functions that fit the eluted peak. A typical peak is shown in Fig.…”
Section: Cross-diffusion Without Reactionmentioning
confidence: 99%
“…[170][171][172] We recently found that cross-diffusion in BZ-AOT microemulsions is quite significant and may therefore be responsible for many of the wealth of patterns observed in this system. 93 A sampling of BZ-AOT patterns is shown in Fig. 4, where we have grouped the most important classes of patterns: wave patterns (upper row and right column), Turing patterns (three left snapshots in the second row), patterns originating from a wave instability (third row), and localized patterns (three left snapshots in the last row).…”
Section: C Cross-diffusion In Physicochemical Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 shows the appearance of convective fingers, which grow upwards and downwards around the interface, in a system where [NaBrO 3 ] B = 0.1 M and [NaBrO 3 ] T = 0 M. Here we assume that the addition of the fourth component in the bottom layer does not change the structural parameters of the microemulsions. 11 The typical growth dynamics of a single finger can be followed and characterized from the space-time (ST) plot depicted in Fig. 2f that is built along the vertical line in Fig.…”
Section: Convective Patternsmentioning
confidence: 99%
“…7 Typical systems in which cross-diffusion-driven reactive patterns can be studied include AOT (sodium bis(2-ethylhexyl)sulfosuccinate aerosol OT) micelles, for which a large number of RD patterns have been characterized 8 and the diffusion matrix often contains large off-diagonal terms. [9][10][11][12] Cross-diffusion effects are also known to be able to trigger convective motions around liquid interfaces in the absence of chemical reactions. Experimental studies of a ternary system, polyvinylpyrrolidone(PVP)-dextran-H 2 O, 13 have indeed demonstrated hydrodynamic instabilities at the miscible interface between non-reactive solutions exhibiting large cross-diffusion properties.…”
Section: Introductionmentioning
confidence: 99%